Stability of anthocyanin extract from riceberry rice bran encapsulated with rice bran protein concentrate under different pH and heating conditions - พาเจริญ สุภาพร (RMUTSB ACADEMIC JOURNAL, 2019)
The objectives of this research were to study the effect of different pH and heating conditions on the stability of anthocyanin extract from riceberry rice bran (RRBE), RRBE encapsulated with maltodextrin (RRBE with MD) and RRBE encapsulated rice bran protein concentrate (RBPc) plus maltodextrin at a ratio of 80:20 by weight (RRBE with RBPc plus MD). The results showed that pH value significantly affected the anthocyanin stability (p<0.05). Anthocyanin was stable at pH 1 and 4; however, it was unstable at pH 9. At pH 9, the losses of anthocyanin in RRBE with RBPc plus MD and RRBE with RBPc plus MD were 42.58 and 22.57, respectively. Temperature or heating levels also significantly affected the anthocyanin stability (p<0.05). After heating at 70, 80 and 90 °C, the results showed that heating at 90 °C, anthocyanin in HRBE was much less stable than that in HRBE encapsulated with RBPc:MD. In overall, the results indicated that encapsulation of HRBE with RBPc:MD could protect against the loss of anthocyanin in HRBE due to the effect of different pH and heating conditions.